Análisis del Centro Histórico de Riobamba y su Impacto en el Imaginario de los Habitantes, periodo octubre 2017 - marzo 2018 - Erazo Tapia, Cristian Paúl (2019)
During the development of this investigation, we were able to know about the conformation and perimeter of the historic center of the city of Riobamba, the real estate with which the riobambeños feel identified, be aware d the impact that this sector of the city has on the imaginary of the inhabitants. In the first chapter, points out the approach of the problem, the general objective and in turn the specific objectives, the justification is also presented. The second chapter, refers to the theoretical framework, where scientific compilations of the various issues raised in the preliminary draft such as: Communication, Culture, Communication Theorics, Social Identity, Cultural Identity, Imaginary, In the third chapter we show the methodological process, the mechanisms and tools that we use for obtaining results. The fourth chapter shows the results of surveys to Riobamba citizens taking into account the sample, this information is detailed in statistical tables and graphs ; We conducted interviews with Patricio Zárate, Director of the Department of Heritage of the GADM of the Riobamba canton, as well as Diego Villacís, Zonal Technical Director of the National Institute of Cultural Heritage (INPC); Similarly Sheets Observation find where we indicate the state that you l find property most representative of the city. The fifth chapter shows the conclusions and recommendations which we obtained thanks to each of the results obtained in the research process and finally in the sixth chapter we have the proposal.